2018
DOI: 10.1002/jemt.22996
|View full text |Cite
|
Sign up to set email alerts
|

Morphological specializations of the epidermis of an angler catfish Chaca chaca (Siluriformes, Chacidae) in relation to its ecological niche: A scanning electron microscopic investigation

Abstract: The present work was undertaken with the aim to deduce morphological adaptations in skin of an angler catfish Chaca chaca by means of scanning electron microscopy. The fish is nocturnal, bottom dwelling, sluggish, ambush predator, lives in sand, mud, or soft substrates often buried and camouflaged for protection and to feed. The surface of the epidermis is covered with polygonal epithelial cells, each having surface relief of microridges forming intricate patterns. In between epithelial cells irregularly distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…In the epidermis of H. hara , the detachment of epithelial cells at the free surface of the OL of the keratinized plaques together with the unculi, from the underlying second‐tier epithelial cells and then their sloughing in the form of sheets on the surface is eloquent. This unique phenomenon is perhaps like what has been reported in the keratinized skin of B. bagarius (Mittal & Banerjee, 1980; Mittal & Munshi, 1970; Mittal et al, 1995) and C. chaca (Mistri et al, 2018a, 2018b). Such an event is neither observed in mucogenic epidermis covering the furrows in the skin of H. hara nor in the skin of a typical fish or a catfish where the epidermis is generally mucogenic.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the epidermis of H. hara , the detachment of epithelial cells at the free surface of the OL of the keratinized plaques together with the unculi, from the underlying second‐tier epithelial cells and then their sloughing in the form of sheets on the surface is eloquent. This unique phenomenon is perhaps like what has been reported in the keratinized skin of B. bagarius (Mittal & Banerjee, 1980; Mittal & Munshi, 1970; Mittal et al, 1995) and C. chaca (Mistri et al, 2018a, 2018b). Such an event is neither observed in mucogenic epidermis covering the furrows in the skin of H. hara nor in the skin of a typical fish or a catfish where the epidermis is generally mucogenic.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, the epidermis in the furrows is mucogenic and Whitear, 1979;Mittal et al, 1995), Bunocephalus verrucosus (Roberts, 1982), C. chaca (Mistri et al, 2018b) and Cypriniformes, such as, Balitoropsis bartschi (Wiley & Collette, 1970), Macrhybopsis hyostoma (Pinion & Conway, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Microridges are apical surface protrusions that are arranged in a unique fingerprint-like pattern or whorls on individual cells of fish epithelium. While microridges have been extensively described in fish skin (Hawkes, 1974;Bereiter-Hahn et al, 1979;Fishelson, 1984;Arellano et al, 2004;Mistri et al, 2018), these structures are found in many other types of teleost tissue. Cornea (Collin and Collin, 1997, 2000, gills (Arellano et al, 2004;Eiras-stofella, 2000;Kumari et al, 2009;Mistri et al, 2016), nasal epithelium (Zeiske et al, 1994;Hansen and Zeiske, 1998), operculum (Mittal et al, 2004), head/ snout epidermis (Rai et al, 2012), and oral mucosa (Uehara et al, 1988(Uehara et al, , 1990Kumari et al, 2005) have all been shown to have microridges protruding from outer surfaces of the superficial layer.…”
mentioning
confidence: 99%
“…The order Siluriformes (catfishes) are a highly diverse (~3900 species, Nelson et al 2016;Fricke et al 2022) group of otophysan fishes that are distributed in freshwaters across the globe and have invaded marine coastal waters on two separate occasions (Lundberg et al 2007). Members of this group are found in both pelagic (Reynolds 1971;Kaatz et al 2010) and benthic environments (Paxton 1997;Mistri et al 2018), with some species capable of traversing across land to find more suitable habitat (e.g., Clarias gariepinus, Johnels 1957). Catfishes also exhibit a wide diversity of life history and reproductive strategies, ranging from broadcast spawners with little or no parental care (Katano 1988;Maehata 2007) to nest guarders and mouthbrooders with large eggs, in which males protect developing embryos (Mayden et al 1980;Barbieri et al 1992).…”
Section: Introductionmentioning
confidence: 99%